2018
DOI: 10.1111/evj.12947
|View full text |Cite
|
Sign up to set email alerts
|

Local mepivacaine before castration of horses under medetomidine isoflurane balanced anaesthesia is effective to reduce perioperative nociception and cytokine release

Abstract: SummaryBackgroundIn horses castration with primary intention healing is usually performed under balanced inhalation anaesthesia. To optimise analgesia, the use of local anaesthesia was tested.ObjectivesTo investigate the effect of local mepivacaine before castration with first intention healing under balanced medetomidine‐isoflurane anaesthesia and flunixin meglumine, morphine analgesia on perioperative cytokine levels and pain in horses.Study designProspective blinded clinical study.MethodsTwenty stallions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 36 publications
(50 reference statements)
2
38
0
Order By: Relevance
“…Four studies confirmed an improvement in surgical quality, with three showing a reduction in anaesthetic agent requirement [25,28,30]. Pain scoring, plasma cortisol or plasma concentrations of inflammatory cytokines (Il-6 and TNFa) were determined in two studies [21,30]. Although there was no difference in cortisol concentrations when lidocaine was used, inflammatory cytokines were lower in animals receiving intratesticular mepivacaine.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Four studies confirmed an improvement in surgical quality, with three showing a reduction in anaesthetic agent requirement [25,28,30]. Pain scoring, plasma cortisol or plasma concentrations of inflammatory cytokines (Il-6 and TNFa) were determined in two studies [21,30]. Although there was no difference in cortisol concentrations when lidocaine was used, inflammatory cytokines were lower in animals receiving intratesticular mepivacaine.…”
Section: Resultsmentioning
confidence: 90%
“…Assessment of pain in the post‐operative period was only established in one study and therefore is the only one to specifically address the question (post‐operative analgesia). One study retained its classification of high quality, two studies were reclassified as moderate quality evidence, two as low quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations